Synthesis of the novel (±)-2-methoxy-6-icosynoic acid – a fatty acid that induces death of neuroblastoma cells - Orellano, Elsie A. (2013)
The first total synthesis for the novel fatty acid (±)-2-methoxy-6-icosynoic acid was accomplished in seven steps and in a 14% overall yield starting from 2-(4-bromobutoxy)- tetrahydro-2H-pyran. The title compound displayed an EC(50) = 23 ± 1 µM against the human SHSY5Y neuroblastoma cell line and an EC(50) = 26 ± 1 µM against the human adenocarcinoma cervix cell line (HeLa) after 48 h of exposure. The corresponding non-methoxylated analog 6- icosynoic acid did not display cytotoxicity (EC(50) > 500 µM) towards the studied cell lines as well as the 2-methoxyicosanoic acid (EC(50) > 300 µM). The critical micelle concentration (CMC = 20–30 µM) for the (±)-2-methoxy-6-icosynoic acid was also determined. It was found that α- methoxylation decreases the CMC of a fatty acid.